2020
DOI: 10.1111/are.14887
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fishmeal with corn protein concentrate in diets for rainbow trout (Oncorhynchus mykiss): Effects on growth performance, physiometabolic responses, and fillet quality

Abstract: Nowadays, aquaculture produces approximately half of the utilized fish globally (Galkanda-arachchige, Wilson, & Davis, 2019). In this regard, fishmeal is the main source of protein in aquaculture nutrition, especially for carnivorous species. Fishmeal not only has high palatability, digestibility and well-adjusted amino acid profile, but also it has some unique properties such as high levels of essential n-3 fatty acids, nucleotides, minerals, phospholipids, vitamins and free of antinutrient factors (Gatlin et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In the present study, the highest growth performance was obtained in P + E treatment that is mainly due to multiple actions of the probiotics and exogenous enzymes. In our study, the high levels of the carcass crude protein and PER in the fish fed with the combination of multi‐strain probiotic and exogenous multi‐enzyme can be explained that the synergistic effect of these two dietary supplements helps fish to pass the consumed protein in its main metabolic pathway (tissue synthesis) (Hosseini Shekarabi et al, 2021; Munir et al, 2016). Moreover, a high LER value and a low carcass fat content of Siberian sturgeon fed with P + E reveal this fact that dietary fats have been used as a primary substrate to provide energy for different metabolic processes instead of storage in the body.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, the highest growth performance was obtained in P + E treatment that is mainly due to multiple actions of the probiotics and exogenous enzymes. In our study, the high levels of the carcass crude protein and PER in the fish fed with the combination of multi‐strain probiotic and exogenous multi‐enzyme can be explained that the synergistic effect of these two dietary supplements helps fish to pass the consumed protein in its main metabolic pathway (tissue synthesis) (Hosseini Shekarabi et al, 2021; Munir et al, 2016). Moreover, a high LER value and a low carcass fat content of Siberian sturgeon fed with P + E reveal this fact that dietary fats have been used as a primary substrate to provide energy for different metabolic processes instead of storage in the body.…”
Section: Discussionmentioning
confidence: 80%
“…Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) represent a pivotal function in the metabolism of amino acids. An increasing trend in the serum shows some inappropriate conditions, including protein malnutrition and ammonia concentration (Hosseini Shekarabi et al, 2020; Xiao et al, 2020). ALT and AST of serum enzyme activities were not markedly different none of the levels of substitution, while Hekmatpour et al (2019) observed an increasing trend of activities these enzymes in higher substitution in the juvenile sobaity seabream, Sparidentex hasta .…”
Section: Discussionmentioning
confidence: 99%
“…The world aquaculture production was increased at an annual growth rate of 4.5% during 2010–2018 and even more in the future (FAO, 2020). On the other hand, the intensification demand of FM in aquaculture practices coupled with decreasing in fish and shellfish natural stocks, which can be accompanied by the escalation of FM cost in the market (Gatlin et al, 2007; Hosseini Shekarabi et al, 2020; Turchini et al, 2009). In recent decades, several studies have been done to substitute FM with plant proteins, while the formulation of plant meals is restricted in aquafeed because of some nutritional deficiencies such as indispensable amino acids (IAAs), presence of antinutritional factors, the potential alimentary tract inflammation, inferior palatability and the conflict with the environmental sustainability due to accelerating of deforestation rates (Francis et al, 2001; Gatlin et al, 2007; Haghbayan & Mehrgan, 2015; Hardy, 2010; Mastoraki et al, 2020; Piccolo et al, 2017; Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%